Bacteriophage activity against and characterisation of avian pathogenic Escherichia coli isolated from colibacillosis cases in Uganda - Kazibwe, George; Katami, Phionah; Alinaitwe, Ruth; Alafi, Stephen; Nanteza, Ann; Nakavuma, Jesca L. (PLoS ONE, 2020)
Avian Pathogenic Escherichia coli (APEC) cause colibacillosis leading to significant economic losses in the poultry industry. This laboratory-based study aimed at establishing stocks of avian pathogenic Escherichia coli lytic bacteriophages, for future development of cocktail products for colibacillosis management. The study determined the antibiotic susceptibility; phylogenetic categories, occurrence of selected serotypes and virulence genes among Escherichia coli stock isolates from chicken colibacillosis cases; and evaluated bacteriophage activity against the bacteria. Escherichia coli characterization was done through phenotypic and multiplex PCR methods. Bacteriophage isolation and preliminary characterization was achieved using the spot assay and overlay plating techniques. Fifty-six (56) isolates were phenotypically confirmed as E. coli and all exhibited resistance to at least one antimicrobial agent; while multi-drug resistance (at least three drugs) was encountered in 50 (89.3%) isolates. The APEC isolates mainly belonged to phylogroups A and D, representing 44.6% and 39.3%, respectively; whereas serotypes O1, O2 and O78 were not detected. Of the 56 isolates, 69.6% harbored at least one virulence gene, while 50% had at least four virulence genes; hence confirmed as APEC. Virulence genes, ompT and iutA were the most frequent in 33 (58.9%) and 32 (57.1%) isolates respectively; while iroN least occurred in 23 (41.1%) isolates. Seven lytic bacteriophages were isolated and their host range, at 1×108 PFU/ml, varied from 1.8% to 17.9% of the 56 APEC isolates, while the combined lytic spectrum was 25%. Phage stability was negatively affected by increasing temperatures with both UPEC04 and UPEC10 phages being undetectable at 70˚C; whereas activity was detected between pH 2 and 12. The high occurrence of APEC isolates resistant against the commonly used antibiotics supports the need for alternative strategies of bacterial infections control in poultry. The low host range exhibited by the phages necessitates search for more candidates before in-depth phage characterization and application.
Keywords: Bacteriophage; poultry